The Resistance Crisis: Characterization and Antimicrobial Challenges of Uropathogenic Bacteria - Kaleem Ullah; Gul, Kainat; Habib, Gul; Ibrar Ul Haq; Riaz, Yashfa; Khan, Amna; Shafiq Ur Rahman; Hayat, Azam; Mujaddad Ur Rehman; Khalil Ullah (Indus Journal of Bioscience Research, 2025)
Urinary tract infections (UTIs) remain a significant clinical challenge, with increasing antibiotic resistance complicating treatment strategies. This cross-sectional study analyzed 124 urine samples from symptomatic UTI patients (84 females, 40 males; mean age 42.5±15.8 years) over a six-month period. Significant bacteriuria (≥10⁵ CFU/mL) was identified in 104 samples (83.9%), which were processed for microbial identification and antibiotic susceptibility testing using standard microbiological techniques and disk diffusion method. Females showed significantly higher UTI prevalence (67.3% vs. 32.7%; χ²=9.83, p=0.002). Gram-negative organisms predominated (87% vs. 13% Gram-positive; χ²=54.15, p<0.001), with Escherichia coli being most prevalent (72%, p<0.001). Carbapenems (meropenem/imipenem) demonstrated 100% susceptibility, while fluoroquinolones exhibited significant resistance (ciprofloxacin 58% vs. moxifloxacin 30%; χ²=12.7, p<0.001). Azithromycin and cefixime showed 10% resistance each. This study highlights the sustained efficacy of carbapenems against uropathogens but reveals concerning resistance to fluoroquinolones, particularly ciprofloxacin. These findings emphasize the need for ongoing antimicrobial surveillance and cautious antibiotic selection in UTI management. This resistance can be reduced by taking precautionary measures like avoiding improper use of antibiotics and self-medication.